Gynecologic Cancer, Cancer Stem Cells, and Possible Targeted Therapies - Keyvani, Vahideh; Riahi, Espanta; Yousefi, Meysam; Esmaeili, Seyed-Alireza; Shafabakhsh, Rana; Moradi Hasan-Abad, Amin; Mahjoubin-Tehran, Maryam; Hamblin, Michael R.; Mollazadeh, Samaneh; Mirzaei, Hamed (Frontiers in Pharmacology, 2022)
Gynecological cancer is one of the main causes of death in women. In this type of cancer, several molecules (oncogenes or tumor suppressor genes) contribute to the tumorigenic process, invasion, metastasis, and resistance to treatment. Based on recent evidence, the detection of molecular changes in these genes could have clinical importance for the early detection and evaluation of tumor grade, as well as the selection of targeted treatment. Researchers have recently focused on cancer stem cells (CSCs) in the treatment of gynecological cancer, because of their ability to induce progression and recurrence of malignancy. This has highlighted the importance of a better understanding of the molecular basis of CSCs. The purpose of this review is to focus on the molecular mechanism of gynecological cancer, and the role of CSCs to discover more specific therapeutic approaches to gynecological cancer treatment.